Avaliação da ação antimicrobiana do Cimento Portland (AACP) e do desempenho do concreto produzido com esgoto doméstico tratado e bruto - Ary Júnior, Ivan José (2018)
Water is an absolute must. The ecological systems that exist on Earth depend on water to sustain life. The human being, by its exponential growth, has been causing the pollution of available fresh water, to the point of promoting its scarcity. The use of domestic sewage treated by concrete manufacturers can be an alternative to save better quality water for human consumption and prevent sewage from being released into the environment, promoting environmental and social advantages. However, to ensure the reuse of water in industry, it is essential to ensure the health of workers and the quality of concrete. This paper proposes to evaluate the use of treated and raw domestic sewage for concrete production, studying the reduction of the risk of the operator when handling it. In the present study, the decay of microbial life was expressive, due to the presence of Antimicrobial Action in Portland Cement - AACP. Its presence significantly reduced the count of thermotolerant coliforms and heterotrophic bacteria from the sewage, indicating a significant antimicrobial activity, classifying it as a sanitizer. In the tests using crude sewage, in order to test the AACP in a more unfavorable situation, when compared to the use of treated sewage, cements of different types and manufacturers were used. For all samples, reductions above 99% were obtained in the counts of these microbiological contaminants. In the assays, the AACP had an antimicrobial effect in a short time, less than 30 minutes, with a broad spectrum performance, which is a relevant fact for the concrete industry. The performance of the concrete produced with drinking water, treated sewage and raw sewage from TEEs in the metropolitan region of Fortaleza, Brazil, was also studied. Concrete and slump test strength tests were performed. In the compressive strength, the values ​​remained the same. With the results of the slump tests it was observed a trend of greater workability in concretes manufactured with effluents. These results indicate the feasibility of its use in the production of concrete, obeying the norms prevailing in the civil construction industry.